To solve this, you need to isolate/get the variable "r" by itself in the equation:
-2(6 - r) = 4 Divide -2 on both sides
![(-2(6-r))/(-2) =(4)/(-2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/b3jvug9ddm8jwgk35rtzcgrryxsstdk07j.png)
6 - r = -2 Subtract 6 on both sides
6 - 6 - r = -2 - 6
-r = -8 Divide -1 on both sides to get "r" by itself
(two negative signs cancel each other out and become positive)
r = 8
PROOF
-2(6 - r) = 4 Substitute/plug in 8 into "r"
-2(6 - 8) = 4
-2(-2) = 4
4 = 4